USING JEOPARDY TO ENHANCE READING COMPREHENSION OF EIGHTH-GRADE STUDENTS AT SMP NEGERI 2 POSO PESISIR UTARA - Husniatul Munawara; Darmawan; Maf'ulah (Universitas Muhammadiyah Makassar, 2025)
Educators are continually looking for better ways to capture students’ interest and help them understand material more effectively, which has brought more attention to interactive learning methods. One approach that has become especially popular is game-based learning, as it helps create lively, engaging, and motivating classroom experiences. This study aimed to investigate the effectiveness of the Jeopardy game in improving reading comprehension among eighth-grade students at SMP Negeri 2 Poso Pesisir Utara. Employing a quasi-experimental design, the research involved two groups: an experimental group of 28 students and a control group of 27 students, selected through cluster random sampling. Data were collected using pre-tests and post-tests administered to both groups. The Independent Samples t-test, conducted via SPSS version 22, revealed a significance value (Sig. 2-tailed) of 0.00, which is below the standard threshold of 0.05. This result led to the rejection of the null hypothesis and confirmed that the Jeopardy game significantly improves students’ reading comprehension.